The EU's raw materials diplomacy: Serbia as a test case. The rule of law and sustainability as benchmarks for Europe's raw materials cooperation - Melanie Müller; Lea Strack; Marina Vulović (Stiftung Wissenschaft und Politik (SWP), 2025)
In July 2024, the European Union (EU) and the Serbian government signed a strategic raw materials partnership. For the EU, this cooperation represents an important step towards diversifying its supply chains and strengthening economic partnerships in its neighbourhood. Serbian President Aleksandar Vuécic has a geopolitical interest in this cooperation, which he also wants to use to further consolidate his already extensive power domestically. The signing of the partnership agreement has triggered massive protests in Serbia. Critics fear that the implementation of the raw materials partnership could further undermine already fragile rule-of-law structures, as well as environmental and social standards. The case of Serbia illustrates that the EU can only exert limited influence on the country's authoritarian government in a geopolitically tense context. However, it must strategically use its available leverage to mitigate the existing risks.
Keywords: 320; Serbia; Aleksandar Vuécic; rule of law; sustainability; Europe's raw materials cooperation; Critical Raw Materials Act (CRMA); ESG (environmental; social; governance); Jadar Project; lithium; boron; German Mineral Resources Agency (DERA); Rio Sava